Right Bundle Branch Block Morphology After Right Ventricular Endocardial Pacing – When Should a Cardiologist Begin to Worry ? - Yadav, Vijay; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Khanal, Raja Ram; Shakya, Smriti; Thapa, Shovit; Sharma, Manju; Adhikari, Suman (Nepalese Heart Journal, 2021)
Even though the left bundle branch block (LBBB) morphology in the surface electrocardiogram (ECG) is expected after right ventricular endocardial pacing, the right bundle branch block (RBBB) morphology may be paradoxically seen in around 8 to 10% of patients. The paced RBBB morphology should be given special attention in terms of safe RV pacing or septal and free wall perforation. Simple techniques such as moving the leads V1-2 to one interspace lower than standard (Klein maneuver) and combining frontal QRS axis between -30° to -90°, precordial transition point at or within V3, and absence of S wave in lead I as an algorithmic approach may correctly identify the pacemaker lead in right ventricle with high sensitivity, specificity, and positive predictive value.